Developing an Intertextual-Based E-Module on Molecular Geometry to Enhance Students’ Conceptual Mastery and Critical Thinking Skills - Hargianti Tri Rahayu; Wiji Wiji; Tuszie Widhiyanti; Sri Mulyani (Jurnal Pendidikan Kimia Indonesia, 2025)
This study aimed to design and develop an intertextual e-module on molecular geometry to overcome limitations related to learning resources and instructional time in schools. The development process followed the ADDIE framework up to the development phase. The e-module was constructed using an intertextual approach that connects macroscopic, submicroscopic, and symbolic representations, thereby facilitating students’ conceptual mastery and fostering critical thinking skills. Validation results revealed that the developed module demonstrated excellent validity, with an average Aiken’s V coefficient of 0.994. The characteristics assessment showed that the self-contained, stand-alone, adaptive, pedagogical, multimedia-integrated, and intertextual features each achieved a perfect Aiken’s V score of 1.000. Furthermore, the self-instructional and user-friendly dimensions obtained scores of 0.992 and 0.972, respectively. Expert evaluations also confirmed strong validity across content (0.844), instructional design (0.960), language (0.808), and media (0.910) aspects. Overall, the findings indicate that the e-module is suitable for implementation as a learning resource and has the potential to improve students’ conceptual mastery and critical thinking skills in molecular geometry.